2001
DOI: 10.1128/jvi.75.20.9696-9702.2001
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Spatial Organization of Potato Virus A Coat Protein Subunits as Assessed by Tritium Bombardment

Abstract: Potato virus A (PVA) particles were bombarded with thermally activated tritium atoms, and the intramolecular distribution of the label in the amino acids of the coat protein was determined to assess their in situ steric accessibility. This method revealed that the N-terminal 15 amino acids of the PVA coat protein and a region comprising amino acids 27 to 50 are the most accessible at the particle surface to labeling with tritium atoms. A model of the spatial arrangement of the PVA coat protein polypeptide chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
56
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 33 publications
5
56
0
Order By: Relevance
“…To understand the mechanism behind such regulation, structural data describing the changes introduced by CK2 phosphorylation into the nucleic acid binding domains of the corresponding proteins are required. Recently, a structural model of PVA CP was proposed on the basis of the experimental data obtained by tritium bombardment combined with theoretical predictions of protein topology ( Baratova et al, 2001). According to this model, the CK2 phosphorylation site Thr-242 is located in an interconnecting loop immediately after the ␤7 strand (amino acids 235 to 241) inside the structural unit commonly found in RNA binding proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To understand the mechanism behind such regulation, structural data describing the changes introduced by CK2 phosphorylation into the nucleic acid binding domains of the corresponding proteins are required. Recently, a structural model of PVA CP was proposed on the basis of the experimental data obtained by tritium bombardment combined with theoretical predictions of protein topology ( Baratova et al, 2001). According to this model, the CK2 phosphorylation site Thr-242 is located in an interconnecting loop immediately after the ␤7 strand (amino acids 235 to 241) inside the structural unit commonly found in RNA binding proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The overall secondary structure of this mutant was compared with that of the wild-type PVA CP us- (A) Scheme of PVA CP and its substitution mutants. The surface-exposed N-and C-terminal domains of the protein (black boxes) are shown together with a predicted abCd structural motif (Baratova et al, 2001) commonly found in RNA binding proteins. The known functions attributed to different regions of the protein (Dolja et al, 1995;Mahajan et al, 1996;Fernández-Fernández et al, 2002) are given below the scheme.…”
Section: Structural Comparison Of Wild-type Pva Cp and Its Ck2 Phosphmentioning
confidence: 99%
“…Most experiments were carried out using the G7 strain, but fiber diffraction experiments used both strains, and because of the better orientation and higher quality of the diffraction data, data from the G6 strain were used in the analysis. The coat proteins of the two strains differ at only 3 amino acid residues (33), and the substitutions are all conservative and within 20 residues of the N terminus, known to be located at the outer surface of the virion and probably disordered (5,56). PVX was purified and stored as previously described (52).…”
Section: Methodsmentioning
confidence: 99%
“…Fourier transform infrared spectroscopy studies of PVX suggest that the virion surface is highly hydrated and that the bound water molecules help to maintain the surface structure of the virion (6). Spectroscopic studies show that coat proteins of potexviruses and potyviruses have similarly high ␣-helical contents (5,31).…”
mentioning
confidence: 99%
“…This was based on the finding that phosphorylation of Potato virus A (PVA; genus Potyvirus) CP downregulates its RNA binding function (11). The phosphorylation site within PVA CP was found to localize to a predicted abCd structural motif (12) common to RNA binding proteins. In addition, a chaperone-mediated ubiquitin degradation pathway has been suggested to limit the amount of CP during the early stages of infection (9).…”
mentioning
confidence: 99%